Outstaring nature's eye the fiction of John McGahern - Sampson, Denis (Catholic Univ. of America Press, 1993)
Although McGahern's fiction is known primarily in Europe, its reception, significance, and place in literary history, especially in the United States, still remain ambiguous and controversial in spite of support from such literary luminaries as John Updike